2005
DOI: 10.1577/t04-050.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surgically Implanted Transmitter Weights on Growth and Swimming Stamina of Small Adult Westslope Cutthroat Trout

Abstract: The generally accepted 2% ratio of transmitter weight to body weight constrains or precludes telemetry studies examining the timing and location of spawning of small adult westslope cutthroat trout Oncorhynchus clarkii lewisi in headwater streams. We empirically determined effects of surgically implanted dummy transmitters ranging in weight from 1 to 5 g on the swimming stamina and growth of small (81.3–206.9 g) adult westslope cutthroat trout in the laboratory to establish acceptable transmitter weights for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 29 publications
(36 reference statements)
2
64
0
Order By: Relevance
“…Another study found no correlation between fish size and cortisol level 24 h or 7 d after implantation of radio tags in juvenile Chinook salmon (length range: 140 mm to 260 mm; tag burden range: 1.3% to 3.5%) [5]. Among other species, it has been recommended that only steelhead O. mykiss parr greater than 74 mm should be implanted with PIT tags [32], and Zale et al [22] did not find a negative influence on mean growth rate or swimming performance of cutthroat trout with tag burdens varying between 0.8% and 5.3%. Thus, our study corroborates the literature from laboratory research in that relative to control fish, the size-specific survival of yearling Chinook salmon with tag burdens up to 5.7 (that is the largest median tag burden per size class encountered in this study) was not affected by the implantation or presence of an acoustic transmitter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found no correlation between fish size and cortisol level 24 h or 7 d after implantation of radio tags in juvenile Chinook salmon (length range: 140 mm to 260 mm; tag burden range: 1.3% to 3.5%) [5]. Among other species, it has been recommended that only steelhead O. mykiss parr greater than 74 mm should be implanted with PIT tags [32], and Zale et al [22] did not find a negative influence on mean growth rate or swimming performance of cutthroat trout with tag burdens varying between 0.8% and 5.3%. Thus, our study corroborates the literature from laboratory research in that relative to control fish, the size-specific survival of yearling Chinook salmon with tag burdens up to 5.7 (that is the largest median tag burden per size class encountered in this study) was not affected by the implantation or presence of an acoustic transmitter.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have attempted to set recommendations and further studies are challenging these recommendations by examining tag effects on salmonids along a range of sizes. Zale et al [22] examined the minimum size at which fish could be tagged without influencing the growth and swimming performance of small cutthroat trout O. clarkii (tag burden range: 0.5% to 5.3%) implanted with dummy radio transmitters. There was no relationship between tag burden and swimming performance, but there were subtle decreases in growth as tag burden increased.…”
Section: Introductionmentioning
confidence: 99%
“…Fish were caught (n ; 20-40 per site) within 50 m of the tributary confluence (in either the tributary, thermal mixing zone, or mainstem) using a combination of angling and electro-fishing, and held in the tributary for a maximum of 12 hours before tagging. We measured fish weight and fork length, and surgically implanted the tags (Lotek's MST-720T temperature-sensor transmitter tags; 1.3 g dry weight; 60.88C) following a tagging protocol similar to Adams et al (1998); tag weight never exceeded 4% of fish body weight (Zale et al 2005). After surgery, fish were held in net-pens within tributaries for recovery for 1 hour prior to release near the area where they were caught.…”
Section: Monitoring Fish Body Temperatures As a Proxy For Habitat Usementioning
confidence: 99%
“…A fundamental assumption of telemetry is that the 1.2 behavior, migration, and physiological state of the fish are not affected by the transmitter presence or tagging process (Skalski et al 2001;Deriso et al 2007). In addition, the transmitter presence or tagging process should not affect fish growth or survival (herein referred to as "tag effects"; Jepsen et al 2002;Zale et al 2005). Tag effect and/or the effect of tagging responses have been a staple of the telemetry literature since 1933 (Markus 1933) and have remained a concern as newer approaches and transmitter technologies have been developed (Moore et al 1990;Jepsen et al 2002;Welch et al 2007).…”
Section: Introductionmentioning
confidence: 99%